2020
DOI: 10.1002/kin.21390
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic reactivities of 7‐L‐4‐nitrobenzofurazans in σ‐complexation processes: Kinetic studies and structure–reactivity relationships

Abstract: The second‐order rate constants (k) for reaction of 7‐chloro‐4‐nitrobenzofurazan 1 and 7‐methoxy‐4‐nitrobenzofurazan 2 with a series of nitroalkyl anions and several of para‐substituted phenoxide anions in aqueous solution at 20 °C have been reported. On the basis of the linear novel approach recently designed by Mayr and coworkers, the electrophilicity parameters E at the C‐5 position of the two nitrobenzofurazans 1 and 2 have been quantified and ranked on the comprehensive electrophilicity scale. Mayr's appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Samples of 7-methoxy-4-nitrobenzofurazan (NBD-OCH 3 ) and 7phenoxy-4-nitrobenzofurazan (NBD-OC 6 H 5 ) were prepared according to the standard methods described in the literature. [27][28][29] The secondary cyclic amines (morpholine, piperidine and pyrrolidine) were commercial products (Aldrich, Darmstadt-Germany) and were redistilled before use whenever necessary.…”
Section: Experimental Details 21 Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples of 7-methoxy-4-nitrobenzofurazan (NBD-OCH 3 ) and 7phenoxy-4-nitrobenzofurazan (NBD-OC 6 H 5 ) were prepared according to the standard methods described in the literature. [27][28][29] The secondary cyclic amines (morpholine, piperidine and pyrrolidine) were commercial products (Aldrich, Darmstadt-Germany) and were redistilled before use whenever necessary.…”
Section: Experimental Details 21 Materialsmentioning
confidence: 99%
“…[24][25][26] Recently, we reported a kinetic study for S N Ar reactions of NBD with secondary amines. [27][28][29][30] The present chapter is focused on the elucidation of the combined experimental-theoretical investigation relationships between the optical (UV-Vis, PL and time resolved photoluminescence (TR-PL), electrochemical (CV) properties and the chemical structures of 4.7-di-substituted benzofurazans (NBDs), based on the kinetic reactivity process of compounds. Parr's approach was employed to develop a relationship which rationalizes the kinetic data previously reported for the reactions of 4-X-7-nitrobenzofurazans with various nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that the 4-nitrobenzochalcogenadiazoles 4, [1][2][3] the 7-L-4-nitrobenzofurazans 5, [4][5][6] and the 2methoxy-3-X-5-nitrothiophene 6 [7][8][9] (Scheme 1) represent a class of neutral electron-deficient substrates which can be described by the experimental model based on the following three-parameter equation (1):…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of anilines in S N Ar and sigma complexation reactions has been examined extensively by several research groups with the aim of understanding the electronic, basicity, and nucleophilic effects of the aniline group 16–19 . More recently, Ben Salah and coworkers 16 have shown that the reactions of N1‐methyl‐4‐nitro‐2,1,3‐benzothiadiazolium tetrafluoroborate 4 with a series of para‐X‐anilines possessing an electron‐withdrawing group (X = H, Cl, and CN) in acetonitrile at 20°C can be described by the linear free‐energy relationship equation (1), where E is the electrophilicity parameter, N is the nucleophilicity parameter, and s N is the nucleophile‐specific slope parameter 20–28 . While the Ben Salah work revealed that a Mayr‐type plot 16 with aniline donors (X = OH, OMe, Me, and H) exhibited an abnormally high slope value, ca.…”
Section: Introductionmentioning
confidence: 99%